Electrocatalysts for Fuel Cells and Hydrogen Evolution Theory to Design - Ray, Abhijit; Mukhopadhyay, Indrajit; Pati, Ranjan K. (IntechOpen, 2018)
The book starts with a theoretical understanding of electrocatalysis in the framework of density functional theory followed by a vivid review of oxygen reduction reactions. A special emphasis has been placed on electrocatalysts for a proton-exchange membrane-based fuel cell where graphene with noble metal dispersion plays a significant role in electron transfer at thermodynamically favourable conditions. The latter part of the book deals with two 2D materials with high economic viability and process ability and MoS2 and WS2 for their prospects in water-splitting from renewable energy.